1995
DOI: 10.1016/0168-6445(94)00052-z
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of oligosaccharides

Abstract: The biological interest of oligosaccharides is growing very rapidly, and necessitates the development of efficient synthesis reactions. The stereo-and regio-selectivity of enzyme catalysis is a key advantage in this field, as a complementary tool to the chemical approach. Two types of enzymes can be applied to the obtention of oligosaccharides: Hydrolytic enzymes, which can catalyze either reverse hydrolysis (thermodynamic control) or transglycosylation (kinetic control) synthesis reactions; and transferase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 18 publications
1
26
0
3
Order By: Relevance
“…The ability of coliforms to utilize prebiotic oligosaccharides has been contradictory. Several studies have reported that FOS can support growth of E. coli, Enterobacter and Salmonella (Wang and Gibson 1993;Hartemink et al 1997), while others have indicated no growth (Hidaka et al 1986;Mitsuoka et al 1987;Bailey et al 1991;Monsan and Paul 1995). VanLaere et al (2000) reported that arabinooligosaccharides could support growth of E. coli but FOS could not.…”
Section: Raffinose Productmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of coliforms to utilize prebiotic oligosaccharides has been contradictory. Several studies have reported that FOS can support growth of E. coli, Enterobacter and Salmonella (Wang and Gibson 1993;Hartemink et al 1997), while others have indicated no growth (Hidaka et al 1986;Mitsuoka et al 1987;Bailey et al 1991;Monsan and Paul 1995). VanLaere et al (2000) reported that arabinooligosaccharides could support growth of E. coli but FOS could not.…”
Section: Raffinose Productmentioning
confidence: 99%
“…Clostridium perfringens is a saccharolytic and pathogenic organism (Sneath 1986) that possesses a wide variety glycosidic enzymes and transporters for carbohydrate utilization (Shimizu et al 2002). It has been reported that C. perfringens cannot use FOS or GOS (Hidaka et al 1986;Monsan and Paul 1995). In contrast, VanLaere et al (2000) reported that a strain of C. perfringens fermented FOS.…”
Section: Raffinose Productmentioning
confidence: 99%
“…Glycosyltranferases (GTFs) are enzymes that catalyse the transfer of glycosyl residues from a donor molecule to a particular acceptor (Monsan and Paul 1995). Many bacteria produce significant amounts of EPSs.…”
Section: Discussionmentioning
confidence: 99%
“…It is readily metabolized to short chain fatty acids by the colonic microbiota (Dills, 1989), being therefore considered as a potential prebiotic. It has been used also as a lactulose substitute in the treatment of hepatic encephalopathy and also as a low-calorie sweetener for diabetics (Monsan and Paul, 1995). Aside from the food sector, lactitol has been used as moisturizing agent, plasticizer and adhesive (Audic et al 2003).…”
Section: Products Derived From Lactosementioning
confidence: 99%
“…Prebiotic action is mostly assigned to GOS-3 and GOS-4 (Gopal et al 2001). Different from other lactose derived NDO, GOS are produced industrially by enzyme biocatalysis with microbial β-galactosidases (Gänzle et al 2008), chemical synthesis having been displaced for being more complex and environmentally objectionable (Monsan and Paul, 1995;Sears and Wong, 2001). The commercial products now available are rather impure preparations, with total GOS amounting about 50% of solids and significant variations, both in the kind of linkage and molecular size distribution, according to the origin of the enzyme used in their synthesis (Rastall, 2006;Crittenden and Playne, 2009 (Husain, 2010;Park and Oh, 2010).…”
Section: Enzymatic Synthesis Of Galacto-oligosacaccharides (Gos)mentioning
confidence: 99%